Adaptive Strategies in Public Communication and Rhetorical Expression: Evaluating the Impact of the MBKM Program at Universitas Muslim Indonesia on Institutional Reputation (2020-2024) - Majid, Abd Majid; Idris, Muhammad; Amir, Izki Fikriani (Al-MUNZIR, 2024)
This research examines public relations practices in universities in relation to the Independent Learning and Campus (MBKM) program, emphasizing the importance of ecosystem management in strengthening institutional reputation and communication systems. The study aims to explore public relations responses to the challenges of the MBKM program through ecosystem-based governance within institutional publicity systems. The researchers employed a qualitative method with an exploratory case study approach to investigate the implementation of the MBKM program over the past two years at Universitas Muslim Indonesia (UMI). Data were collected through in-depth interviews, participatory observation, focus group discussions, and analysis of policy documents and publications. Data credibility was ensured through triangulation, member checks, and team discussions. The findings indicate that university public relations adaptively utilize communication skills to manage both internal programs and external collaborations with businesses, industries, and student exchange programs supported by the Ministry of Education. Public information is continuously disseminated through the university’s website, social media, and other online platforms. The university's public communication system adopts a structural and cultural approach aligned with institutional regulations to support public information disclosure while enhancing the institution's academic reputation. Keywords: Adaptive; Public Communications; Rhetoric